The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.rasd.2020.101629
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary testing of the Dutch version of the Program for the Education and Enrichment of Relational Skills (PEERS®)

Abstract: The content of interventions targeting social behavior is sensitive to cultural differences in etiquette and societal customs. Here we describe (1) the process of linguistic and cultural adaptation of the PEERS® social skills program to the Dutch language and culture, and (2) the results from a preliminary adaptation test among 32 adolescents (12-18 years old) with autism spectrum disorder (ASD). Although some important cultural adaptations were made, the similarities in effective social behaviors across cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For instance, a study modified the PEERS® model for Dutch culture and observed different reactions to gossip in Dutch and American adolescents. Americans appeared surprised, questioning the significance of gossip, while the Dutch remained indifferent, displaying no reaction [ 49 ]. These cultural distinctions emphasize the necessity for developing culturally sensitive VR-based social skills training for diverse populations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study modified the PEERS® model for Dutch culture and observed different reactions to gossip in Dutch and American adolescents. Americans appeared surprised, questioning the significance of gossip, while the Dutch remained indifferent, displaying no reaction [ 49 ]. These cultural distinctions emphasize the necessity for developing culturally sensitive VR-based social skills training for diverse populations.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the sample size of the studies was small. Fourth, there was an extreme variability in terms of clinical and socio-demographic characteristics [15,63]. Fifth, we decided to use a relatively narrow search strategy to identify only studies assessing the effects of LEGO ® -based therapy on ASD; following this, some studies may have been missed if they used terms such as neurodevelopmental disorders or social communication problems; however, on the other hand, our decision allowed us to increase the specificity of the intervention target.…”
Section: Discussionmentioning
confidence: 99%
“…Parents act as a social coach for the implementation of these skills in natural settings. In the Netherlands, the PEERS® manual was translated and adapted by a team of 15 mental health care professionals [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the Netherlands, the culturally adapted version of PEERS® has yielded promising preliminary results in a pilot-study [ 15 , 16 ]. Apart from the linguistic adaptation, minor adjustments were made for the Dutch version, including culture specific examples of social groups, activities, social networking sites, jokes as well as wording for teasing comebacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation